2016
DOI: 10.1107/s2414314616019787
|View full text |Cite
|
Sign up to set email alerts
|

2-Methyl-3-(3-methylisoxazol-5-yl)-4-oxo-4H-pyrido[1,2-a]pyrimidin-1-ium chloride

Abstract: In the title molecular salt, C13H12N3O2+·Cl−, the oxazolyl ring is disordered over two orientations in a 0.536 (15):0.464 (15) ratio, both of which approximate to envelopes with the N atom as the flap in each case. The cation and anion are linked by a charge-assisted N—H...Cl hydrogen bond. In the extended structure, C—H...N, C—H...O and C—H...Cl interactions link the components into a three-dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The thermodynamic activation parameters such as the activation apparent energy E a , the activation enthalpy ∆H* and the activation entropy ΔS* were calculated from the Arrhenius equation (4) and the transition state equation 5 The energies of the activations of the three compounds are superior to those of the acid medium. This result confirms that our molecules are adsorbed into the surface of the metal by forming physical bonds (physisorption) [46]. Furthermore, positive signs of activation enthalpies revels the endothermic nature of the process of dissolving steel.…”
Section: Thermodynamic Parameters Of the Activation Corrosionsupporting
confidence: 81%
“…The thermodynamic activation parameters such as the activation apparent energy E a , the activation enthalpy ∆H* and the activation entropy ΔS* were calculated from the Arrhenius equation (4) and the transition state equation 5 The energies of the activations of the three compounds are superior to those of the acid medium. This result confirms that our molecules are adsorbed into the surface of the metal by forming physical bonds (physisorption) [46]. Furthermore, positive signs of activation enthalpies revels the endothermic nature of the process of dissolving steel.…”
Section: Thermodynamic Parameters Of the Activation Corrosionsupporting
confidence: 81%
“…[20] We have also showed that the heterocyclic β-diketone 4 has been condensed with a variety of nucleophilic reagents to give new heterocyclic systems containing pyridopyridine, pyrazole, isoxazole, hydroxyl-quinazoline moieties. [21][22][23][24] In continuation of our research work in this area, we studied the condensation of compound 4 with 5-amino-3-cyano-4-methyl-pyrazole 1 in refluxing ethanol for 24 hr. The reaction leads to the formation of the unexpected bipyrazolopyrimidine 3 next to pyridopyrimidinone 6 which were separated by silica gel column chromatography to afford 45% of compound 3 and 8% of 6 (Scheme 2).…”
Section: Plausible Mechanism Of the Synthesis Ofmentioning
confidence: 99%
“…The adsorption isotherm describes the type of interaction between the molecules of the inhibitors (FM1, FM2 and FM3) and the MS surface. The FMs molecules adsorb on MS/solution interface by the dislocation of water molecules as shown [10]:…”
Section: Adsorption Isothermmentioning
confidence: 99%